A Study to Delineate the Immunohistological Parameters of Active Versus Stable Vitiligo Using S100, Melan A in Conjunction with CD4 and CD8 Immunohistochemistry Markers - Sai Jyoti; Minakshi Bhardwaj; Savitha Sharath; Kabir Sardana; Pooja Arora (Indian Dermatology Online Journal)
Background: Vitiligo is an autoimmune pigmentary disorder where it is important to assess the disease status (active/stable) to guide therapeutic decisions. Aim and Objectives: We aimed to compare expression of Melan A and S100 in active and stable vitiligo lesions and correlate them with CD4 and CD8 T cells. Patients and Methods: Skin biopsies from 45 clinically diagnosed vitiligo patients (25 active and 20 stable) were taken for histopathological analysis. Immunohistochemistry expression for Langerhans cells (S-100), melanocytes (Melan A), and CD4 and CD8 T cells was compared between active and stable vitiligo. Results: Basal cell layer vacuolization and dermal melanophages were more common in active vitiligo (P = 0.003). S100 and CD8 expression were increased in active cases, while CD4 and CD4/CD8 ratio were more in stable cases. A moderate positive correlation between Melan A with CD8 (P = 0.019) and S100 with CD4 (P = 0.013) in active vitiligo was noted. Limitations: The limitations of the study include small sample size and lack of control group. There could also be a chance of recall bias in the history given by patient regarding the duration of activity which may have resulted in the misclassification of active versus stable vitiligo. Conclusion: We found increased disease activity in the center and margins of active lesions of vitiligo, which can be discerned by decreased expression of Melan A and CD4 as well as an increased expression of S100 and CD8 with concomitant increased basal cell layer vacuolization and dermal melanophages.